Anthropic impact assessment of coastal ecosystems in the municipality of Puerto Colombia, NE Colombia (2019)
Bolívar, M.; Rivillas-Ospina, G.; Fuentes, W.; Guzmán, A.; Otero, L.; Ruiz, G.; Silva, R.; Mendoza, E.; Maza, M.; García, L., and Berrío, Y., 2019. Anthropic impact assessment on coastal ecosystems in the municipality of Puerto Colombia, NE Colombia. In: Silva, R.; Martínez, M.L.; Chávez, V., and Lithgow, D. (eds.), Integrating Biophysical Components in Coastal Engineering Practices. Journal of Coastal Research, Special Issue No. 92, pp. 112–120. Coconut Creek (Florida), ISSN 0749-0208. Human activity, mainly associated with the construction of coastal infrastructure, has caused ecological degradation to the coastal zone at Puerto Colombia, Colombia. Severe erosion attacked the ancient sandy spit that protected the municipality from wave energy to an extent that it completely disappeared. The groins constructed thereafter, with the aim of protecting the coast, have exacerbated the sediment imbalance, affecting the Balboa coastal wetland. At present, the coastline around Puerto Colombia is highly vulnerable; the remaining ecosystems are under severe pressure, and the population is at risk. Restoring the marine and terrestrial connectivity is key to improving this situation. ©Coastal Education and Research Foundation, Inc. 2019.